Sosialisasi Pengembangan UMKM Melalui Pemanfaatan Teknologi Informasi Di Desa Kasindir - Sylvia Vianty Ranita; Khairun Nisa Lestari; Rita Handayani (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Kasindir Village is one of the villages in Jorlang Hataran District, Kabupaten Simalungun, Sumatera Utara. Kasindir Village is a village that carries out agricultural, livestock, and trade activities. Kasindir Village has great potential for developing MSMEs in the village. The development of MSMEs is considered capable of realizing a sustainable economy and supporting local governments in the Sustainable Development Goals (SDG's) program, especially in poverty and hunger eradication programs, sustainable economic growth, and employment. Community service implementers in Kasindir Village observed that MSME actors still require understanding and knowledge on utilizing information technology to advance their businesses. This includes packaging attractive products, providing the latest innovations, and promoting on social media to expand their market. MSME strategy development is able to realize the spirit of the SDGs. In this activity, the methods used to carry out community service activities are socialization and observation methods. Some of the problems faced by creative MSMEs in Kasindir Village include limited capital, raw materials, the use of very simple production equipment, and limited marketing media. Therefore, various parties, both government and private, need to provide support through sustainable business development programs.